Early neurological development and nutritional status in Mexican socially deprived contexts. - Edson Serván-Mori; Evelyn Fuentes-Rivera; Amado D Quezada; Carlos Pineda-Antunez; María Del Carmen Hernández-Chávez; Angélica García-Martínez; Abby Madrigal; Raquel García-Feregrino; Tania Santiago-Angelino; María Hernández-Serrato; Lourdes Schnaas (PLoS ONE)
Early childhood development (ECD) is a critical stage in the intergenerational process of human development. Targeted interventions depend on accurate and up-to-date ECD measurements. This paper presents estimates for the nutritional and neurodevelopmental status of socially marginalized children in Mexico. We performed a cross-sectional study based on data collected in 2019-2020 during home visits to 1,176 children aged 0-38 months across 24 highly marginalized locations in Oaxaca. We assessed nutritional status according to the World Health Organization 2006 child-growth standards and ECD status using the Child Development Evaluation Test, 2nd Edition. We stratified results by sex. Prevalence of stunting was 5.3 percentage points (p.p.) higher (p = 0.023) in males (25.3%; 95% CI: 20.2%, 31.1%) compared to females (20.0%; 95% CI: 15.0%, 26.1%). Overall prevalence rates stood at 5.7% (95% CI: 4.0%, 8.1%) for underweight, 1.5% (95% CI: 0.9%, 2.7%) for wasting and 3.6% (95% CI: 2.3%, 5.7%) for overweight/obesity, with no significant differences by sex. Prevalence of normal development was 8.3 p.p. lower (p = 0.001) in males (39.3%; 95% CI: 34.5%, 44.4%) compared to females (47.6%; 95% CI: 41.6%, 53.6%). By development area, the highest prevalence of suboptimal outcomes among children with developmental lag or at risk of delay was observed in their gross motor and language skills: 24.1% (95% CI: 20.0%, 28.8%) and 38.6% (95% CI: 34.0%, 43.3%), respectively. The largest difference between the sexes was found in the language area. Our results show that childhood development strategies have been insufficient thus far in the studied population. Programs specifically designed to prevent ECD lags and bridge inequality gaps are urgently needed. Trial registration: ClinicalTrials.gov ID: NCT04210362.